(untitled) (Research, Society and Development, 2020)
Accounting professionals, alongside managers, are experiencing constant moments of evolution, and one of them are the new measures adopted by the tax authorities in the constitution of new systems and ancillary obligations to improve the monitoring of company movements and prevent fraudulent operations. The newest requirement, called Block K, consist in the submission of the Production Control and Inventory Logbook from industries and companies similar to industries. Through this obligation it is possible to monitor the entire production chain of companies, from inputs to the finished product. The new measures adopted will reflect on the companies’ procedures because it will be necessary to review the production and inventory control management. This study aims to demonstrate the perception of accountants and managers regarding the new ancillary obligation. To achieve the proposed goal, it is initially applied a bibliographic research based on books and virtual materials, and is applied a questionnaire to managers and accounting professionals in the city of Nova Serrana-MG, in order to test the hypotheses raised. Subsequently, it was found that companies will undergo changes in organizational culture, but the tool will positively assist managers in inventory control, not being considered a tool just to meet the needs of tax authorities.